Use of Ficus Septica Leaf Extract for Biological Control of Anthracnose Disease in Carica Papaya Caused by Colletotrichum spp - Sudirga, S.K.; Parwanayoni, N.M.S. (KnE Life Sciences, 2022)
The fig (Ficus septica) is a widespread wild plant whose leaf extract contains bioactive compounds with antifungal properties, including alkaloid and phenolic compounds, both of which are antioxidants. Colletothricum spp. is a pathogenic fungus found in cultivated plants that can cause anthracnose, a plant disease. Papaya (Carica papaya) is one of the cultivated plants that frequently displays symptoms of anthracnose disease caused by Colletothricum spp. The focus of this research was to determine whether F. septica leaf extract could inhibit the growth of Colletothricum spp. on C. papaya. The antifungal activity of F. septica leaf extract against Colletothricum spp. was measured using the well diffusion method. The extract concentrations, which were determined by measuring the extract’s MIC value, were 0.5%, 1%, 2%, 3%, 4% and 5% (b/v), with methanol and synthetic fungicides serving as controls. According to the findings, the MIC value of the F. septica leaf extract on Colletothricum spp. growth was 0.4%, with an inhibition zone of 2.37 mm. Meanwhile, the inhibition zones formed by the F. septica leaf extract treatment were 2.5 mm, 3.4 mm, 7.6 mm, 9.7 mm, 12.7 mm, and 13.5 mm, respectively, and 0 mm for the negative control and 30 mm for the positive control. According to the analysis of variance results, all of the treatments produced results that were significantly different from those of the negative control, and the 4% extract was the most effective in vitro. We conclude that F. septica crude leaf extract contains bioactive compounds with antifungal properties and it can be used as a safe alternative to control Carica papaya anthracnose disease. Keywords: anthracnose, Carica papaya, Colletothricum spp., Ficus septica.